Analysis of the diagnostic and prognostic value of Peripheral blood mononuclear cell microRNA-9-5p in patients with sepsis in the intensive care unit - Ye, Haoming; Wang, Ruojue; Ji, Qiang; Li, Qianru; Liang, Jinquan; Liu, Miao; Cao, Limian; Shao, Min (Frontiers in Cellular and Infection Microbiology, 2025)
ObjectiveTo investigate the diagnostic and prognostic value of miR-9-5p in peripheral blood mononuclear cells in sepsis patients.MethodsDifferentially expressed miR-9-5p in sepsis were screened from a database and available literature. Subsequently, iBMDM cell validation was conducted and the expression level of miR-9-5p in peripheral blood mononuclear cells was determined using RT-qPCR in 69 sepsis patients and 30 non-sepsis patients with infections, 24 hours after ICU admission. A control group that comprised 35 healthy individuals, matched for age and sex, was set up from those who agreed to provide blood samples laboratory analysis.ResultsOn admission to the ICU, the levels of miR-9-5p were significantly higher in sepsis patients (10.13 [3.21, 24.94]) than in non-sepsis patients with infections (2.08 [1.68, 3.18]) and healthy controls (0.86 [0.36, 1.88]) (p < 0.001). The miR-9-5p levels were positively correlated with the severity of the disease as indicated by the SOFA score (r=0.656, P<0.001). The AUC of miR-9-5p in predicting sepsis, septic shock, and in-hospital death was 0.825, 0.821, and 0.845, respectively.ConclusionElevated expression levels of miR-9-5p in peripheral blood mononuclear cells are significantly associated with an increased risk of sepsis and septic shock, and also indicate a higher risk of organ dysfunction.